P994Does AF always beget AF? Retrospective study in patients with complex cardiac devices. (18th June 2020) - Briosa E Gala, A; Pope, M; Leo, M; Betts, T R
Abstract: Introduction: Atrial fibrillation (AF) is conventionally divided in paroxysmal AF (PAF) and persistent AF (PersAF) according to episode duration, with a perceived inevitable progression of the arrhythmia in most patients: "AF begets AF". This dichotomous classification of AF is currently being challenged by continuous monitoring with implantable cardiac monitors and pacemakers which suggest different patterns of AF with considerable variation in AF burden.  Purpose: This study sought to examine the long-term progression of AF burden in patients with complex cardiac devices (implantable cardiac defibrillators [ICD] and cardiac resynchronisation therapy-defibrillators [CRT-D]). Methods: This retrospective study examined the weekly AF burden in patients with ICDs and CRT-Ds and on remote monitoring between January 2010 and July 2019.  All transmissions and electrograms were assessed for the presence of AF lasting more than 6 minutes.  The first episode of AF determined was considered follow-up year 0.  PersAF was defined as a weekly AF burden of 100%. Medical records were reviewed for baseline characteristics at the time of the first episode of AF and interventions that may affect burden such as direct current cardioversion (DCCV) and catheter ablations. Results: Of 331 patients on remote monitoring, 106 (32%) had evidence of AF. Of these, 89% were male, age 64 ± 12 years, BMI 30 ± 6 kg/m2, LA diameter 4.5 ± 0.8 cm, 58% had an ICD, 10% had previous AF ablation and 27% had antiarrhythmic medication. Forty-six (43%) had PersAF and 60 (57%) had PAF over a total follow-up of 393 patient years (mean follow-up 4.6. ±2.1).  The mean AF burden  was 1.2 ± 4.4% in PAF and 66.4 ± 35.3% in PersAF at the end of the first year of follow-up. When compared to year 1, the mean annual AF burden did not increase in the PAF and PersAF groups. Moreover, the PersAF patients had a significant reduction in the mean annual AF burden up to year 7 of follow-up. In year 8, the mean annual AF burden remained below year 1; however, due to a low number of patients (5) it did not reach statistical significance (mean difference 15.1%, p = 0.06) . To further assess individual progression in PersAF patients, the annual AF burden was subdivided in 4 categories (<25%, 25%-50%, 50%-75% and >75%). In 30 (65%) patients it remained unchanged, in 5(11%) it worsened and in 11 (24%) it improved (Figure ). Moreover, 35 (76%) patients reverted to sinus rhythm following their first episode of PersAF (5 following DCCV and 2 after catheter ablation).  Conclusions: In this cohort,   the mean AF burden did not increase; in fact, we observed a significant reduction in patients with PersAF despite a low rate of interventions. These findings reinforce the emerging concept of AF as a heterogenous disease with various phenotypes that challenge the current simplistic binary classification.